2007
DOI: 10.1002/bit.21352
|View full text |Cite
|
Sign up to set email alerts
|

Efficient bioremediation of total organic carbon (TOC) in integrated aquaculture system by marine sponge Hymeniacidon perleve

Abstract: The aim of this study is to investigate the potential of using marine sponge Hymeniacidon perleve to remove total organic carbon (TOC) in integrated aquaculture ecosystems. In sterilized natural seawater (SNSW) with different concentrations of TOC, H. perleve removed approximately 44-61% TOC during 24 h, with retention rates of ca. 0.19-1.06 mg/h .g-fresh sponge, however no particulate selectivity was observed. The highest initial TOC concentration, in which about 2.7 g fresh sponges could remove TOC effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Previous studies on H. perlevis have suggested that this sponge is extremely plastic, being able to grow at either the intertidal or within the sublittoral, to feed on a wide variety of particulate sources, and to heal wounds and regenerate from small pieces at extremely rapid rates (Fu et al, 2006(Fu et al, , 2007Maldonado et al, 2010b). Individuals used in the laboratory experiments grew at the intertidal zone of Lingshui (38ยฐ32 0 33.77 00 N, 121ยฐ32 0 33.77 00 E; Yellow Sea, Dalian, China), where they become periodically exposed to air, also to temperatures as high as 40ยฐC during summer low tides and as low as -10ยฐC during winter.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on H. perlevis have suggested that this sponge is extremely plastic, being able to grow at either the intertidal or within the sublittoral, to feed on a wide variety of particulate sources, and to heal wounds and regenerate from small pieces at extremely rapid rates (Fu et al, 2006(Fu et al, , 2007Maldonado et al, 2010b). Individuals used in the laboratory experiments grew at the intertidal zone of Lingshui (38ยฐ32 0 33.77 00 N, 121ยฐ32 0 33.77 00 E; Yellow Sea, Dalian, China), where they become periodically exposed to air, also to temperatures as high as 40ยฐC during summer low tides and as low as -10ยฐC during winter.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, compared with other major commercial filter feeders, S. clava has the following advantages used in bioremediation: (1) S. clava seldom serves as bait for other animals in the sea, so the various pollutants in its body filtered from seawater, such as heavy metal and pesticide residue, are seldom transmitted in the food chain, which results in less pollution in the sea and suggests their greater potential as environmental remedy for the sea; (2) compared with filter feeding shellfish, S. clava is more capable of filtering water and excreting less nitrogen, its ammonia excretion rate being reported as 0.97-2.13 lg/h/g of dry weight, lower than Crassostrea gigas (2.40-13.20 lg/h/g of dry weight) and Argopecten irradians (6.16-29.8 lg/h/g of dry weight) by Wang et al(1998); (3) S. clava is immune to contamination showing great vitality, and it is found that while the scallops at the same ecological niche succumb to death at a large scale, S. clava multiplies each year; (4) Compared with sponges (Fu et al 2007), sessile S. clava gathers at a larger amount easier to be collected and harvested (Jiang et al 2008). S. clava has been successfully cultured in Dalian and Yantai of China, and it is the ideal organism for the aquaculture water body bioremediation along the coast.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the sponges have been reported to be suitable bioremediators for organic matter and microbial contaminants (Donovan et al 2009;Fu et al 2006;Fu et al 2007;Longo et al 2010;Zhang et al 2010). However, investigations on removing organohalogen compounds are rare.…”
Section: Introductionmentioning
confidence: 98%